Assessment of Types of Violence among Adolescents - Sajem, kareem; Sajem, kareem; Sajem, kareem; Khalifa, mohammed; sajed, kareem (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): To assess the types of violence among adolescents in Baghdad City. A descripƟve study which was using the assessment approach was conducted on purposive sample of 60 parents of adolescent for identify types of adolescents violence in their families, was selected according to specific criteria for participating in health education program towards adolescents’ violence control in Baghdad city. Methodology: A questionnaire was constructed for the purpose of the study. It was consisted of two parts; the first part which included the parents’ demographic characteristics for parents (sex, age, educational level and socioeconomic status); the second part included types of adolescent violence that reported by parents. Data were collected through the interview technique with the parents in the homes, health care centers, and school, from November, 1st 2008 to December, 31st 2008. Data were analyzed through use of descripƟve analysis (Frequencies and percentages). Results: The results of the study indicated that the majority of adolescents had physical and psychological violence. So, there was no sexual violence. The study concluded that adolescents’ violence is a problem, because it was definitely impacted on health of adolescents and their families. Recommendations: The study recommends that studies and programs can be designed and implemented on the parents and adolescents or together for resolve conflicts, problem–solving approaches and how to prevent risk factors which contribute in adolescents’ violence.